2015
DOI: 10.1016/j.jplph.2015.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and enzymatic responses to oxidative stress induced by pre-harvest water supply reduction and ripening on mango (Mangifera indica L. cv. ‘Cogshall’) in relation to carotenoid content

Abstract: The effects of a reduction in water supply during fruit development and postharvest fruit ripening on the oxidative status and the antioxidant defense system were studied in the mango fruit (Mangifera indica L.) cv. Cogshall. Changes in non-enzymatic (ascorbate) and enzymatic (SOD, CAT, APX, MDHAR, DHAR and GR) antioxidants, as well as oxidative parameters (H2O2 and MDA) and major carotenoids, were measured in unripe and ripe fruits from well-irrigated and non-irrigated trees. Under non-limiting water supply c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…The peroxidation level of protein-lipid membranes in plant organisms is commonly determined on the basis of malondialdehyde content. Thus, the MDA content is one of the most important indices, always determined in the study of oxidative stress level in plants subjected to the influence of different stress factors (Liu et al 2013 , 2014 ; Rosalie et al 2015 ; Radošević et al 2015 ). In the present paper, no considerable changes of MDA content of spring barley seedlings were observed between controls and samples cultivated on the soil with the addition of ILs.…”
Section: Resultsmentioning
confidence: 99%
“…The peroxidation level of protein-lipid membranes in plant organisms is commonly determined on the basis of malondialdehyde content. Thus, the MDA content is one of the most important indices, always determined in the study of oxidative stress level in plants subjected to the influence of different stress factors (Liu et al 2013 , 2014 ; Rosalie et al 2015 ; Radošević et al 2015 ). In the present paper, no considerable changes of MDA content of spring barley seedlings were observed between controls and samples cultivated on the soil with the addition of ILs.…”
Section: Resultsmentioning
confidence: 99%
“…Reactive oxygen species generation is part of the cellular metabolism, and depending on the levels of production and the ROS type, they could have either toxic effects or signal properties. There are evidences that ROS metabolism is involved in a diverse range of plant processes, and the available data indicate that fruit development and ripening have an active ROS metabolism in different species such as grapevine berry (Pilati et al, 2014), mango (Rosalie et al, 2015), peach (Huan et al, 2016), tomato (Kumar et al, 2016;Zhu et al, 2017), grape berry (Xi et al, 2017), or guava (Mondal et al, 2009;Batista-Silva et al, 2018). In previous reports on sweet pepper ripening, we focused on the H 2 O 2 metabolism, and it was found that catalase activity and their gene expression were diminished during ripening.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in MDA content in plant cells is an indisputable index of oxidative stress and indirectly reflects the degree of cell damage. Therefore, the level of MDA is always determined when studying the extent of oxidative stress in plants subjected to different stressful biotic and abiotic factors (Liu et al, 2013;Rachoski et al, 2015;Rosalie et al, 2015).…”
Section: Effect Of Qas On the Generation Rate H 2 O 2 And Lipid Peroxmentioning
confidence: 99%